The prognostic signifi cance of normal technetium-99m MIBI myocardial perfusion spect imaging over a four-year follow-up period - Neethling, Hans J; van Heerden, Ben B; Klopper, Johannes F; Ellmann, Annare (SA Heart Journal, 2017)
normal Tc-99m MIBI myocardial perfusion study has previously been shown to indicate a benign prognosis. Our aim was to determine the longer term prognosis of a normal study in our patient population. Methods: A retrospective evaluation of 209 patients with a normal Tc-99m MIBI study was performed. Follow-up data was obtained in 157 patients, with complete follow-up in 121 (mean follow-up period of 56 months). In 36 patients only partial follow-up was possible (32 months follow-up). No follow-up data, except for the possible registration of deaths, could be obtained in 52. Patients were evaluated for the occurrence of primary or secondary cardiac events. Results: The study group had a moderate pre-test probability for coronary artery disease (48 + 30.7%). Two possible cardiac deaths occurred (cardiac death rate of 0.95%). No primary events occurred in the group with complete follow-up, but 6 secondary events were recorded (cardiac event rate of 4.9%). No primary or secondary events occurred in the partial follow-up group during the follow-up period. The incidence of secondary or non-fatal primary events in this group for the period after they were lost to follow-up or in the group with no follow-up could not be ascertained. There was, however, no statistically significant difference between these groups regarding age, pre-test probability and exercise parameters. Conclusion: Similar to the findings with Tl-201, our study indicates a favourable longer term prognosis after a normal Tc-99m MIBI study.